A Bibliometric Analysis of Online Prosocial Behavior Research - Gayatri, Putu Angita; Rahmah, Nailur; Raffles, Fatihah (Faculty of Psychology Universitas Gadjah Mada, 2025)
Online prosocial behavior is an important topic in digital psychology, yet bibliometric studies on this subject remain limited. This study aimed to analyze publication trends and map key themes in online prosocial behavior research. Descriptive bibliometric analysis and thematic mapping were conducted using Biblioshiny (Bibliometrix) in the R software package. Additionally, international collaboration networks were examined through VOSviewer using a country-based co-authorship method. A total of 40 bibliographic records were retrieved from the Scopus database using keywords related to online prosocial behavior from 2011 to 2025. The findings highlight research landscapes, including the most influential authors, leading affiliations and countries, emerging research trends, temporal development, and frequently cited articles. Thematic mapping reveals core themes, such as online prosocial behavior, human, motivation, well-being, behavioral, and social interaction. This study highlights global trends and research directions on online prosocial behavior, emphasizing the importance of context in examining this phenomenon, particularly within the Indonesian setting. Furthermore, from a practical perspective, the findings may serve as a reference for the development of digital literacy programs for adolescents.